Functional characterization of MFSD3 in auditory system and zebrafish embryogenesis - Ma, Ying; Qiu, Shi-Wei; Wang, Wei-Qian; Feng, Hai-Feng; Zheng, Lu; Wei, Ge-Ge; Nie, Hui-Yi; Yang, Jin-Yuan; Chen, Yi-Jin; Dai, Pu; Gao, Xue; Yuan, Yong-Yi (Frontiers in Genetics, 2025)
The solute carriers (SLCs) are important membrane-bound transporters that regulate cellular nutrition, metabolism, homeostasis and survival. Emerging evidence highlights the critical involvement of SLCs in auditory physiology. To date, over ten SLC family members have been linked to hearing function. MFSD3 (also known as SLC33A2), is a putative plasma membrane-localized acetyl-CoA transporter regulating lipid metabolism and energy homeostasis. It has been found to be associated with the pathogenesis of neurodegenerative dementia and tumor progression. Nevertheless, its potential role in hearing remains unexplored. In this study, through qRT-PCR, we demonstrated that mfsd3 was predominantly expressed during early embryonic development in zebrafish. Morpholino-mediated mfsd3 knockdown in zebrafish induced inner ear malformations (hypoplastic otic vesicles, reduced otolith size) and hair cells loss in lateral line neuromasts. Additionally, Mfsd3 deficiency led to developmental defects (pericardial edema, body axis curvature) and impaired locomotor activity in zebrafish. The qRT-PCR analysis further revealed significant upregulation of key Wnt/β-catenin pathway components (dkk1b, wnt8a, lrp6, frzb and COX2) in mfsd3 knockdown zebrafish. Our findings suggest MFSD3 as a potential participant in auditory function and embryogenesis, with implications for understanding hearing loss pathogenesis.